Magnetoencephalography reveals an increased non-target P3a, but not target P3b, that is associated with high non-clinical psychosocial deficits. (30th January 2018) - Ford, Talitha C.; Woods, Will; Crewther, David P.
Abstract: Auditory processing deficits are frequently identified in autism and schizophrenia, and the two disorders have been shown to share psychosocial difficulties. This study used magnetoencephalography to investigate auditory processing differences for those with a high degree of a non-clinical autistic and schizotypal trait phenotype, Social Disorganisation (SD). Participants were 18 low (9 female) and 19 high (9 female) SD scorers (18–40 years) who completed a three-stimulus auditory oddball paradigm of speech sounds (standard: 100 ms 'o', deviant: 150 ms 'o', novel: 150 ms 'e'). Spatio-temporal cluster analysis revealed increased amplitude for the high SD group in a left ( p = 0.006) and a right ( p = 0.020) hemisphere cluster in response to the novel non-target. No cluster differences were found in response to the target deviant. These findings suggest that those with a high degree of the SD phenotype recruit more cortical resources when processing unattended, novel speech stimuli, which may lead to psychosocial deficits. Highlights: Autism and schizotypal spectra share a trait phenotype, Social Disorganisation (SD). High SD scorers have increased left and right P3am to non-target speech sounds. Increased P3am localised to frontal, insular, anterior cingulate and tem-poral regions. No group difference in P3bm to target speech sound. Psychosocial deficits associated with aberrant non-target speech sound processing.